Development and parameter estimation of a compact electronic wedge brake test rig using grey box system identification - Che Hasan, Mohd Hanif; Hassan, M. Kabir; Ahmad, Fauzi; Marhaban, Mohammad Hamiruce; S.I. Haris (Penerbit Universiti Teknikal Malaysia Melaka, 2023)
This article presented the development and model parameter estimation of a compact electronic wedge brake (EWB) test through mathematical modelling and system identification (SI). The EWB test rig was vast and complex, leading to high costs and time consumption. Additionally, the EWB parameters estimation was limitedly discussed. Thus, a compact test rig was developed to produce up to 300N of braking force, which was acceptable to demonstrate the effectiveness of the model and EWB performance. Two separate transfer function models for the motor and EWB mechanism were proposed. The parameter estimation was made using the grey box approach, which combined mathematical modelling and SI. The complete physical parameters value via two separated SI was successfully obtained. The brake responses were analysed by comparing the simulation and experiment under rapid control prototyping (RCP). The average percentage of root mean square error (RMSE) value between the simulation and experiment was less than 6.23%. The test rig configuration and proposed model guarantees were helpful in preparing a simpler, low-cost brake test rig and provided an alternative way to obtain model physical parameter values.